Heart recovery from a brain‐dead donor with a history of Ravitch procedure for repair of pectus excavatum. Issue 12 (23rd October 2022) - Grunfeld, Matan; Ohira, Suguru; Choe, Joshua; Lanier, Gregg M.; Martin, Kathryn; Spielvogel, David; Kai, Masashi
Abstract: Background: We describe the successful heart transplantation of a brain‐dead male donor with a remote history of pectus excavatum repair. Method and Results: On computed tomography, the ascending aorta was in close proximity to metallic struts from the donor's sternal repair. Before harvesting the heart, visual and digital inspections revealed minimal space between the sternum and ascending aorta, complicated by severe adhesions in the lower sternum. After the pericardium was opened, the subsequent recovery of the heart was performed in a standard fashion. At one‐year post‐transplant, the recipient continues to have normal graft function. Conclusions: Careful evaluation, intraoperative consideration, and coordination with other transplant teams were essential in the successful recovery of the heart during a time of organ shortages.